Cost Utility of Breast Tissue Expansion using Carbon Dioxide versus Saline: An Analysis of Infection Risk. Issue 10 (October 2019) - Chopra, Karan; Slavin, Benjamin; Khavanin, Nima; Kraenzlin, Franca; Darrach, Halley; Holton, Luther; Landford, Wilmina N.; Singh, Devinder P.
Abstract : Background: The AeroForm System, a needle-free, patient-controlled carbon dioxide-filled tissue expander, represents a novel option for tissue expansion in 2-stage breast reconstruction. This technology has previously been found to decrease time to expansion, health-care utilization, and infection rates. The purpose of this study was to determine the economic impact of the reduced infection rate observed with the AeroForm tissue expander as compared with saline tissue expansion. Methods: A decision model incorporating costs, quality-adjusted life years, and clinical outcomes of infection was designed to evaluate the cost-efficacy of AeroForm tissue expanders versus conventional saline expanders. All statistical calculations were performed in the R statistical computing environment. Results: Pooled infection rates from the published literature following saline and AeroForm tissue expander placement were 5.83% and 2.62%, respectively. Cost-utility analysis resulted in a baseline expected savings of $253.29 and an expected gain of 0.00122 quality-adjusted life years with AeroForm tissue expanders. One-way sensitivity analysis revealed that AeroForm tissue expanders were dominant when the surgical site infection rate was greater than 4.56% with traditional saline expanders. Conclusions: Clinical benefits of an innovation are no longer sufficient to justify its acquisition costs. Novel technologies must also demonstrate favorable economic outcomes. This cost-utility analysis demonstrates that the use of AeroForm expanders is likely a cost-saving technology for 2-stage breast reconstruction.